NEW PRIVATE PRACTICE PARADIGMS IN PAKISTAN - Hamid Mahmood; Mohammad Aslam; Sadia Aslam (Journal of University Medical & Dental College, 2016)
ABSTRACT: INTRODUCTION: The medical private practice is changing quickly due to many reasons. Most of practitioners need a comfortable environment and working conditions to deliver healthcare services to the patients. Multi specialty clinics, owned by private entrepreneurs, have been established in the big cities to earn maximum revenue. The small GP clinics are very difficult to be established in big cities. The revenue earned by the small clinics is very low as compared to their expenses such as rent, utility bills & paramedical staff payments. It is the need of the time that complete revised private practices paradigms should be developed. OBJECTIVE: To find out (1) future employment structure of the doctors in private sector. (2) To find out whether single specialty clinics are better than multi specialty clinics in the future scenario PERIOD OF STUDY: January 2014 to March 2016. RESULTS: The landscape of medical practice is changing very quickly. Various practice options requires financial and legal knowledge of the various fields. New health commission reforms have provided a platform for healthy competition among the competing physicians and surgeons. CONCLUSIONS: It has been found out that the private practice has taken the shape of industry. All the resources should be used carefully to earn the maximum revenue for meeting the requirement of all stakeholders. The change in the private practices paradigms is very huge which is very difficult for the general practitioners and single specialty clinics to adopt. FUTURE RECOMMENDATIONS: The private practicing paradigms have changed in the big cities. The GP practice is on the decline in the big cities. Future prospects for multispecialty clinics with diagnostics facilities seem to be most important for future practice. It is the need of the day that the doctors must learn administrative and financial controls techniques to maximize revenue to survive in private practice.